(untitled) (Communication & Society, 2012)
This article discusses the relation between Chilean youth media consumption patterns and their disposition to vote. In this context, to what extent does news consumption and entertainment by Chilean youth influence their political participation patterns? Based on data from a national survey (N=1.000) of young individuals between 18 and 29 years old in the three major urban cities in Chile, we conclude that individuals’ news consumption and Facebook use are positively related to their disposition to vote. However, the consumption of entertainment news has a negative effect on individuals’ political participation practices.